2018
DOI: 10.1002/hep.30297
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Prevalence of Hepatitis C Virus Infection in the United States, 2013‐2016

Abstract: Hepatitis C virus (HCV) infection is the most commonly reported bloodborne infection in the United States, causing substantial morbidity and mortality and costing billions of dollars annually. To update the estimated HCV prevalence among all adults aged ≥18 years in the United States, we analyzed 2013‐2016 data from the National Health and Nutrition Examination Survey (NHANES) to estimate the prevalence of HCV in the noninstitutionalized civilian population and used a combination of literature reviews and popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
381
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(397 citation statements)
references
References 31 publications
(47 reference statements)
9
381
5
2
Order By: Relevance
“…An estimated 2.4 million adults were living with chronic hepatitis C virus (HCV) infection in the United States in 2013‐2016 . HCV prevalence is highest among persons born between 1945 and 1965 (2.6%), persons who inject drugs, males, non‐Hispanic Black persons, and persons with less education and family income . Only 55.6% of people with chronic HCV infection are aware of their infection .…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 2.4 million adults were living with chronic hepatitis C virus (HCV) infection in the United States in 2013‐2016 . HCV prevalence is highest among persons born between 1945 and 1965 (2.6%), persons who inject drugs, males, non‐Hispanic Black persons, and persons with less education and family income . Only 55.6% of people with chronic HCV infection are aware of their infection .…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis reported global HCV prevalence of 2.5%, ranging from 1.3% in the Americas to 2.9% in Africa . In the United States, an epidemiological study of the National Health and Nutrition Examination Survey (NHANES) revealed serologic antibody positivity in 1.7% (4.1 million) adults, with viremia seen in 1.0% (2.4 million) in 2013 to 2016 . In 2017, the Centers for Disease Control estimated 44,700 new cases of acute HCV infection, with an estimated 2.8 million people with chronic HCV in the United States…”
Section: Hepatitis C: From Chronic Malady To Robust Curementioning
confidence: 99%
“…(4) In the United States, an epidemiological study of the National Health and Nutrition Examination Survey (NHANES) revealed serologic antibody positivity in 1.7% (4.1 million) adults, with viremia seen in 1.0% (2.4 million) in 2013 to 2016. (5) In 2017, the Centers for Disease Control estimated 44,700 new cases of acute HCV infection, with an estimated 2.8 million people with chronic HCV in the United States. (6) In the United States, although the disease burden from HCV is decreasing, the clinical characteristics of those with chronic infection is evolving.…”
Section: Changing Epidemiology and Screening Recommendationsmentioning
confidence: 99%
“…Hofmeister identified populations with heightened hepatitis C virus (HCV) prevalence, including 2.1 million individuals incarcerated as of December 31, 2016, (1) estimating this population's HCV prevalence at 9.5× that of householders surveyed by the National Health and Nutrition Epidemiology Survey (NHANES). Yearly, the United States incarcerates 10 million people; subtracting 2.1 million incarcerated persons leaves 7.9 million in the NHANES frame who were recently released from prison/jail prior to the 1-day count (3% of all U.S. adults).…”
Section: To the Editormentioning
confidence: 99%
“…Spaulding and her colleagues raise a number of reasons why our study may underestimate the true prevalence of hepatitis C among incarcerated persons, but unfortunately, no nationwide data exist to assess the magnitude of these potential biases. According to 2016 Bureau of Justice Statistics data, most people arrested are detained in jails for short periods of time (1) ; thus, most of the number of persons cited in Dr. Spaulding's reply would be eligible for NHANES sampling. We could not further adjust estimates for potential nonresponse bias beyond those addressed through standard NHANES sample weights without risk of double-counting prevalent cases.…”
Section: Replymentioning
confidence: 99%